Application of a high percentage of reclaimed asphalt pavement in an asphalt mixture: blending process and performance investigation. Issue 3 (4th May 2017) - Yu, Bin; Gu, Xingyu; Wu, Ming; Ni, Fujian
Abstract : This study performed a laboratory investigation of applying a high percentage of reclaimed asphalt pavement (RAP, up to 50%) in an asphalt mixture. The properties of aged binder were first determined and the rejuvenator and SBR latex were used to restore the binder properties. The optimum dosages of the rejuvenator and SBR additive are 2% and 4% of aged binder mass, respectively. Then the preheating temperatures of aggregate were determined according to the RAP content to meet the mixture temperature requirement. The effects of the blending process, especially the feeding sequence of materials, on the mixture performances were investigated to recommend the optimum blending process. The water durability, low-, high-temperature and fatigue performances of the mixture containing 30%, 40% and 50% RAP were examined and it was found that with the further addition of polyester fibre, the performances of an asphalt mixture containing 50% RAP can satisfy the engineering requirement.